Migration Crisis in West Africa: Limits and Prospects of Political Regulation - Ivan A. Zakharov; Maksim M. Agafoshin; Stanislav A. Gorokhov (Vestnik RUDN. International Relations)
The study examines the limits and prospects of political regulation of the migration crisis in West Africa. The authors characterize the migration situation in the countries of the region, analyze the available political instruments of the Economic Community of West African States (ECOWAS) that facilitate the migration processes in the region. Furthermore, the efficacy of these instruments in addressing the growing number of refugees and internally displaced persons (IDPs), which could potentially precipitate a humanitarian crisis, is evaluated. The analysis of the migration situation in West Africa is based on an extensive statistical database that provides the information on the number and structure of migrants, including refugees and IDPs, as well as on the direction of migration flows. Special attention is paid to the instruments of political regulation of migration processes available to ECOWAS, and the analysis is based on international legal documents (protocols, declarations, agreements, etc.), which constitute the core of the regional migration policy. The intensification of forced migrations in West Africa, provoked by interrelated and aggravating threats, including armed conflicts and natural disasters, has resulted in a significant migration crisis in the region. The analysis of the legal framework of migration policy at the ECOWAS level reveals that this international organization is responding quite quickly to the massive increase in the number of refugees and IDPs. The ECOWAS migration policy is distinguished by a high level of elaboration, taking into account all the main provisions of regional and global agreements regulating migration issues. Despite its progressive nature, the migration policy of the organization is not flawless since it pursues conflicting sets of tasks, namely integration and securitization. The first set of tasks is aimed at ensuring the economic integration of West African countries, which implies an increase in population mobility. The second set of tasks is aimed at strengthening the control over migration flows and encapsulating them within the region. At the same time, the ECOWAS migration policy does not contain a sufficient number of specific mechanisms for overcoming migration crises. The lack of financial and human resources in the countries of West Africa determines the high level of involvement of international organizations in the development of the migration policy of ECOWAS. The example of the Rabat Process, whose development is strongly influenced by the European Union (EU), illustrates that a number of external political actors are more interested in encapsulating the migration crisis in West Africa than in solving it. In other words, the potential of ECOWAS is being used by external political actors to achieve the goals of their own migration policies. In the future, this could lead to an escalation of conflicts in West Africa, provoking an even larger migration crisis and promoting inter-regional disagreements.